Poor Bone Quality in Patients With Amyotrophic Lateral Sclerosis - Caplliure-Llopis, Jordi; Escrivá, Dolores; Benlloch, María; de la Rubia Ortí, José Enrique; Estrela, José María; Barrios, Carlos (Frontiers in Neurology, 2020)
Objective: Musculoskeletal functional deterioration in Amyotrophic lateral sclerosis (ALS) is associated with an increase in bone fractures. The purpose of this study was to evaluate the influence of sex, ALS type, on bone quality in patients with ALS compared to healthy controls. The impact on bone health of the clinical status and some metabolic parameters was also analyzed in ALS patients. Methods: A series of 33 voluntary patients with ALS, and 66 healthy individuals matched in sex and age underwent assessment of bone mass quality using quantitative ultrasound (QUS) of the calcaneus. Ultrasonic broadband attenuation (BUA), the speed of sound (SOS), stiffness index and T-score were measured. Bone mineral density (BMD) was estimated using standard equations. Apart from fat and muscle mass percentage determinations, clinical baseline measures in ALS patients included ALSFRS-R score, Barthel index for activities of daily living, pulmonary function measured using FVC, and muscular strength assessed by a modified MRC grading scale. Laboratory tests included serum calcium, 25-HO-cholecalciferol (Vitamin D), alkaline phosphatase (ALP), T4 and TSH. Results: All bone parameters evaluated were statistically significant lower in ALS patients than in healthy controls. ALS females showed significantly lower bone parameters than healthy females. According to the estimated BMD, there were 25 ALS patients (75.8%) and 36 (54.5%) healthy individuals showing an osteoporotic profile (BMD <0.700 g/cm2). Only 16.7% of the ALS females had T-scores indicative of healthy bones. There was no correlation between any of the clinical parameters analyzed and the bone QUS measurements. Vitamin D and TSH levels positively correlated with all the bone parameters. Conclusions: This study confirms that ALS patients, particularly females, exhibited deteriorated bone health as compared to healthy individuals. These structural bone changes were independent of ALS subtype and clinical status. Bone health in ALS patients seems to be related to certain metabolic parameters such as Vitamin D and TSH levels.